Study on the Damage Model of Coal Rock Caused by Hydraulic Pressure and Electrical Impulse in Borehole. (24th May 2021) - Bao, Xiankai; Cao, Jiaxing; Zheng, Wenxiang; Guo, Junyu; Liu, Yuan; Zhao, Jinchang
Abstract : The purpose of this study is to study the damage and fracturing effects of high-voltage discharge on coal-rock mass under the action of hydrostatic pressure. Based on the traditional damage evolution model and the change of the effective bearing area and stress around the microcrack of coal-rock mass on a microscopic scale, the expression of macroscopic damage variation of coal-rock mass under the action of electrohydraulic coupling was derived, and its damage constitutive relation was established. The high-voltage pulse water shock stress test of coal-rock mass under the conditions of different water pressures and voltages was carried out, and its damage numerical model was established by the ABAQUS/XFEM. The damage variable values of coal-rock mass with different electrohydraulic parameters were compared to characterize the generation and expansion of internal macroscopic cracks. From the results, it is shown that the damage variable based on the effective bearing area and stress around the crack can represent the morphology and expansion change of crack of coal-rock mass with different electrohydraulic parameters clearly and quantitatively. Different hydrostatic pressures and discharge voltages have influence on the damage variables of coal-rock mass, but different influencing degrees cause different damages on coal-rock mass. The damage of coal rock can be characterized by the change of the effective bearing area and stress around microcracks in coal body. So, stress testing and numerical simulation have verified the correctness of the damage model.